Toxicity testing of impurities and metabolites - Black, Kurt (Henry Stewart Talks, 2009)
Types of impurities and regulatory framework, Qualification of impurities, Special considerations for genotoxic impurities, Residual solvents and drug product degradants, Safety assessment of drug metabolites